Fabricate And Investigate The Performance Of Alumina Based Ceramic Cutting Tool With Different Edge - Mat Amin, Mohd Imran (2018)
The research in this project focused on the comparison performance between two cutting tools with different edge. Both cutting tools will be fabricated based on the alumina powder processing with round and sharp edges. For each cutting tool, a special mould will be utilized according to the required shape. Specific weight of alumina powder will be processed with ball mill and poured into the designated mould to produce the green body of alumina inserts. These green bodies will be sintered at proposed 1400oC with 9 hours soaking time to produce refractory solid ceramic inserts. The mechanical properties of both insert will be examined according to the density, hardness and dimensions. The cutting tools will be further tested in tool wear evaluation by machining with AISI 1045 with variation of cutting speeds and feed rates around 200-250 m/min and 0.1-0.125 mm/rev respectively, while depth of cut will be kept constant at 0.5 mm. The wear at the edge of both inserts will be monitored with optical microscope and further scrutinized using Scanning Electron Microscope for failure modes analysis. On the same time, the surface roughness will be assessing using surface roughness tester and optical microscope to differentiate the surface characteristics machined by the cutting tools fabricated. The results from this study should be useful to develop alumina based cutting tool for low cost and small scale machining operations.